Enzymatic interactions between Gremmeniella abietina var. abietina, European race, and two resistant hosts, Pinus banksiana and P. contorta. Issue 1 (7th August 2012) - Simard, M.; Laflamme, G.; Rioux, D.; Woodward, S.
Summary Ultrastructural observations showed that the European race of Gremmeniella abietina var. abietina can secrete several cell wall–degrading enzymes that help the invasion of Pinus banksiana and P. contorta shoot tip tissues. Alterations in the content or distribution of cellulose were obvious, indicating that colonization might be achieved primarily through the action of glucanases. Polygalacturonases seemed more abundant in the cortex and the phloem of the stem, suggesting they are among the first enzymes secreted by the pathogen during infection. Production of laccases and peroxidases was also revealed but always close to fungal cells or in areas where host wall degradation was obvious. In places where there was an accumulation of phenolic compounds in the infected zones of the shoot, particularly in or near the transition zone, immunolocalization of both enzymes was limited or absent. Laccases and polygalacturonases were regularly detected over the extracellular sheath of G. abietina, and this indicates that the sheath could play a significant role during host wall degradation. Finally, examination of G. abietina wall constituents, such as chitin and β‐1, 3‐glucans, suggests that the composition of the pathogen wall changes during the infection process. This change may be associated with the secretion of fungal enzymes but could also be linked to host reactions altering the integrity of pathogen cell walls.